(untitled) (Research, Society and Development, 2021)
This article aims to highlight doctrinal aspects relevant to the institute of the family and its nuances in the Brazilian legal system. The addressed the expected aspects of the familiar field the legislation will also be addressed, as well as dealing with affectivity as a fundamental principle of this institute. The research is based on bibliographic references, consulting current legislation, of a qualitative nature, permeating the conceptualization of the theme, highlighting its conceptual aspects. In this way, in the end, he reflects on the family field, its evolution from the legal system to the collectivity.